The Role of Management Institution of the Ciremai Mountain National Park in Encouraging Public Participation - Yuyun Yuningsih; Herdis Herdiansyah (Politeknik Negeri Bali, 2019)
The Ciremai Mountain National Park area is one of the national park areas in Indonesia that must be maintained. The enormous potential of biodiversity and environmental services are stored in it. Sustainability of the Ceremai Mountain National Park (TNGC) is an important part of increasing regional and national resilience in climate change mitigation efforts. This study aims to determine the role of the TNGC area management institution in motivating people around the area to actively participate in managing forests. The study was conducted by observation, interviews, and literature studies with a qualitative approach. Based on the results of the study it is known that the management of TNGC area is carried out to support education and science, research, activities that support cultivation, culture, and also tourism. In addition, the function of management of conservation areas is based on the conservation of natural resources, forests with the principles of protection, preservation and utilization can be realized and managed optimally, sustainably, and wisely. The involvement of the community in the management of the TNGC area is still very minimal, so that the sense of community ownership of the TNGC area is still low. Therefore optimization of community involvement is needed so that management can run optimally and provide greater benefits for communities around the area.